Copper effects in mechanical, thermal and electrical properties of rapidly solidified eutectic Sn-Ag alloy - Gumaan, Mohammed S.; Shalaby, Rizk Mostafa; Ali, Esmail Abdo Mohammed; Kamal, Mustafa (Springer Nature, 2018)
The Sn-3.5 wt%Ag alloy considered as a good alternative to Pb-Sn alloys. This study aims to investigate the effects of Cu or Sb additions by 3 or 5 wt% to melt-spun Sn-3.5%Ag alloy. Ternary melt-spun Sn-Ag-Cu and Sn-Ag-Sb alloys investigated using X-ray diffractions (XRD), Scanning electron microscope (SEM), Dynamic resonance technique (DRT), Instron machine, Vickers hardness tester and Differential scanning calorimetry (DSC). The results revealed that the microstructures of the ?-Sn phase, Ag3Sn and Cu3Sn intermetallic compounds (IMCs) in the solder matrices were refined due to the effect of Cu additions and melt-spun process. Moreover, increasing Cu content promotes Ag3Sn intermetallic compound (IMC) formation. Consequently, the addition of 3 wt% of Cu reduced the creep rate ? from (3.79??10?3) to (1.65??10?3) and delayed the fracture point. The tensile results showed an improvement in Youngs modulus by 47% (30.3 GPa), ultimate tensile strength (UST) by 11.6% (23.9 MPa), and in toughness by 20.5% (952.32 J/m3) compared to the eutectic Sn-Ag alloy. Vickers hardness has improved by 3.3% (136.71 MPa) and thermal activation energy by 54% (90.40 KJ/mol) when compared with that of eutectic Sn-Ag alloy. Those improvements are related to the lack of lattice strain from 7.56??10?4 without 3 wt% of Cu to 5.26??10?4 with 3 wt% of Cu. Its melting temperature (Tm) increased by 3 C due to Ag3Sn IMC increased and Cu3Sn formation, but the pasty rang (mushy zone) decreased by 4 C with 3 wt% of Cu. The small lattice strains resulted with 3 wt% of Cu made the electrical resistivity of this alloy more stable at elevated temperatures. The mechanical, thermal and electrical improvements of Sn93.5-Ag3.5-Cu3 alloy provide good physical performance for soldering process and electronic assembly.